Effects of maternal exercise on infant mesenchymal stem cell mitochondrial function, insulin action, and body composition in infancy - Filip Jevtovic; Donghai Zheng; Alex Claiborne; Ericka M. Biagioni; Breanna L. Wisseman; Polina M. Krassovskaia; David N. Collier; Christy Isler; James E. DeVente; P. Darrell Neufer; Joseph A. Houmard; Linda E. May (Physiological Reports, 2024)
Abstract Maternal exercise (ME) has been established as a useful non‐pharmacological intervention to improve infant metabolic health; however, mechanistic insight behind these adaptations remains mostly confined to animal models. Infant mesenchymal stem cells (MSCs) give rise to infant tissues (e.g., skeletal muscle), and remain involved in mature tissue maintenance. Importantly, these cells maintain metabolic characteristics of an offspring donor and provide a model for the investigation of mechanisms behind infant metabolic health improvements. We used undifferentiated MSC to investigate if ME affects infant MSC mitochondrial function and insulin action, and if these adaptations are associated with lower infant adiposity. We found that infants from exercising mothers have improvements in MSC insulin signaling related to higher MSC respiration and fat oxidation, and expression and activation of energy‐sensing and redox‐sensitive proteins. Further, we found that infants exposed to exercise in utero were leaner at 1 month of age, with a significant inverse correlation between infant MSC respiration and infant adiposity at 6 months of age. These data suggest that infants from exercising mothers are relatively leaner, and this is associated with higher infant MSC mitochondrial respiration, fat use, and insulin action.